(3JMQjQ cJGH CUhd GdgfOSI hGdMSGH dChbdjOSs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , (B672 (3g` s; (3GbdjOSs
(3ChdgG (B:s
,(3HYO adeG aQZJ Yf JMQjQ GdeLSWi QCjJ Gf CMQQ cJGH CUhd GdgfOSI hGdMSGH GdefShH Edi ChbdjOS s
(3BNQgG (B:s
(3hEfeG de ChQOg ai GdcJGH dchfg eHjfkG Ydi eG gh NGQL hGddg Gdehab hGdeYjf s
(3GdfSNI HgG MhGTs
(3fSNI NGeSIs
(3JHUQI GdYfhGf (B:s
(3JQLeI(B/(3fbds
(3eUOQ GbJfGA GdCUd (B:s
(3Bjg Gddg GdMcje GdYGeg (B_ (3GdfLa (B(387) s
Keywords: (3GdQjGVjGJs